Evaluating The Quality Of E-Learning At Tishreen University From The Point Of View Of Graduate Students (A Field Study For Graduate Students In The Faculty Of Economics) - جنبلاط, مادلين (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study problem centered on the following question: What is the reality of the quality of e-learning in the Faculty of Economics at Tishreen University? The study also aimed at the following: Explaining the concept of e-learning and the degree of its culture spread among graduate students in the Faculty of Economics, determining the degree to which faculty members in the Faculty of Economics at Tishreen University use e-learning, determining the availability of the necessary software for e-learning and the degree of its use by faculty members in Faculty of Economics at Tishreen University, and a statement of the reality of the electronic infrastructure in the Faculty of Economics at Tishreen University. The descriptive analytical approach was used, and the data were studied and analyzed using the SPSS program. After analyzing the data, the study reached a set of results, the most important of which are the following: a decrease in students' ability to deal with e-learning, a decrease in the ability of faculty members to apply e-learning, and a decrease in The level of the quality of the infrastructure and the electronic software needed for e-learning, and a decrease in the administrative quality of e-learning at Tishreen University from the viewpoint of graduate students.